Ethical Dilemmas for Dental Students in Greece - Maria Antoniadou; Evangelia Masoura; Marina Devetziadou; Christos Rahiotis (MDPI AG, 2023)
Professional dental ethics for students are based on promoting oral health for dental patients and reinforcing an anthropocentric approach to communication and dental services. A total of 133 dental students (males 33.8% N1 = 46, females 66.2% N2 = 87) completed the study questionnaire. Descriptive statistics were applied, and non-parametric Kruskal-Wallis tests were used (p < 0.05). Students refuse services to patients that misbehave (37.6%), have irrational demands (18%), and when clinical cases exceed their capabilities (36.8%). Of the participants, 50.4% want to waive confidentiality when abuse is declared. Ethical role models are educators (33.8%), other qualified dentists (25.6%), and their parents (21.8%). Female gender positively affects integrity (p = 0.046), altruism (p = 0.032), and difficulty in conversations among colleagues (p = 0.036). Students outside the capital are less interested in esthetic issues (p = 0.007), in giving more than one treatment plan (p = 0.006), and in being confronted with inadequate treatments from other colleagues (p = 0.005). Family income positively affects clinical skills (p = 0.003), trust issues (p = 0.008), and moral insight and intuition (p = 0.02). Presentation with clinical scenarios is the preferred educational method (49.6%). Dental students show compassion for poor patients, respect patients' autonomy, and guide patients to choose the best treatment plan before receiving dental ethics seminars. There is a positive relationship between the ethical footprints of students and gender, origin, family income, postgraduate studies, and future professional plans. Factors and ways to incorporate ethics in the dental curriculum could be considered when planning relevant courses.